1999
DOI: 10.1055/s-0038-1634175
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Genetic Algorithms and Other Classification Methods in the Diagnosis of Female Urinary Incontinence

Abstract: Galactica, a newly developed machine-learning system that utilizes a genetic algorithm for learning, was compared with discriminant analysis, logistic regression, k-means cluster analysis, a C4.5 decision-tree generator and a random bit climber hill-climbing algorithm. The methods were evaluated in the diagnosis of female urinary incontinence in terms of prediction accuracy of classifiers, on the basis of patient data. The best methods were discriminant analysis, logistic regression, C4.5 and Galactica. Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 11 publications
0
2
1
Order By: Relevance
“…This result is quite below the 96% accuracy obtained by the discriminant analysis model in the study where two other types of UI were also classified (Laurikkala et al, 1999). In addition to the fact that the data used by Laurikkala et al were categorical, it is not clear if the reported performance was a test or validation accuracy, which, in the latter case, would provide an over-optimistic performance metric.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…This result is quite below the 96% accuracy obtained by the discriminant analysis model in the study where two other types of UI were also classified (Laurikkala et al, 1999). In addition to the fact that the data used by Laurikkala et al were categorical, it is not clear if the reported performance was a test or validation accuracy, which, in the latter case, would provide an over-optimistic performance metric.…”
Section: Discussioncontrasting
confidence: 64%
“…In a previous study, the k-means, discriminant analysis, LR, decision tree, and two genetic algorithms were compared when diagnosing three types of incontinence (Laurikkala et al, 1999), including stress UI. The data were categorical and obtained through clinical questionnaires and exams.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation